Evolutionary Significance of Equinae From the Mexican Neogene - Bravo-Cuevas, Victor Manuel; Jiménez-Hidalgo, Eduardo (Frontiers in Ecology and Evolution, 2019)
North American Equinae integrates a monophyletic clade that consists of about 20 genera and 80 species. This group includes horses with hypsodont cheek teeth belonging to the merychippines and the tribes Hipparionini, Protohippini, and Equini. The primary adaptive radiation and diversification of Equinae occurred in the Neogene period (23.03 – 2.53 Ma). In Mexico, 11 genera and 20 species of Neogene Equinae have been reported, which correspond to 55% and 28% of the generic and specific diversity in North America, respectively. The Mexican record exhibited their major diversity during the late Miocene (10 species) and evidences part of the evolutionary history of North American Equinae, as it is stated in the following considerations: (1) The presence of merychippine species from the late Hemingfordian – early Barstovian (18 – 15 Ma) of southern Mexico (“Merychippus” cf. primus and “M.” cf. sejunctus) that are related with earliest representatives of Equinae in North America. (2) The occurrence of populations referable to Cormohipparion aff. quinni, Calippus sp., and Pliohippus sp. from the early – late Barstovian (15 – 14 Ma) of southern Mexico, which are synchronous with the first known appearances of those genera from the Great Plains and Gulf Coastal Plain in the United States. (3) The equine horse Dinohippus mexicanus from the late Hemphillian (4.8 Ma) of central and northern Mexico that is considered the closest sister species of primitive Equus. These records suggest that early differentiation of some hipparionines, protohippines, and equines may have had occurred also in areas of southern tropical North America during the middle Miocene; furthermore, the origin of primitive Equus could be traced from the Mexican record.